Experimental Examination of Performance, Exhaust Emission and Combustion Behaviours of A Ci Engine Fuelled With Biodiesel/Diesel Fuel Blends - Alaattin Osman Emiroğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The main objective of thisstudy is to evaluate the effect on diesel engine performance, exhaust emissionand combustion characteristics of canola oil biodiesel. The biodiesel wasblended with petroleum-based diesel fuel (DF) by 10% (B10), 20% (B20) and 50%(B50) volumetrically. Engine tests were carried out on a direct injection,single-cylinder, compression ignition engine at different engine loads and theresults were compared with the reference DF. The results showed that themaximum cylinder pressure and heat release rate values of DF were higher thanthose of the biodiesel blends at all engine loads. The addition of biodiesel toDF increased the brake specific fuel consumption (BSFC) and decreased the brakethermal efficiency (BTE) at all engine loads. In addition, biodiesel blendscaused a slight increase in nitrogen oxide (NOx) emissions whilecausing a decrease in smoke opacity and carbon monoxide (CO) emissions.